ANALISIS PENYEBAB PENGANGGURAN LULUSAN SEKOLAH KEJURUAN DI JAWA BARAT DAN GARUT - Aditya Aprilliofany (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
Today to meet economic needs must obtain proper and appropriate employment. Every business owner, be it from large companies to small entrepreneurs, must have certain criteria in recruiting their workforce. In Indonesia, vocational schools are one solution for individuals to be able to quickly get a job after graduating from their education. The fact is that vocational schools in Indonesia rank first with the largest unemployment rate (TPT) compared to other levels of education. Not only in Indonesia, vocational school graduates also have the largest TPT in West Java Province and Garut Regency. The aim of this research is to find out what factors influence unemployment of vocational school graduates in the Province of West Java and Garut Regency. The research uses two kinds of analysis, namely descriptive analysis and quantitative analysis, the quantitative analysis used here is binary logistic regression analysis. The dependent variable of the study is the employment status of vocational school graduates, namely unemployment or work, while the independent variables are age, gender, status in the household, marital status, area classification, and classification of majors.